Modeling the binding of fulvic acid by goethite: the speciation of adsorbed FA molecules - Filius, Jeroen D.; Meeussen, Johannes C.L.; Lumsdon, David G.; Hiemstra, Tjisse; van Riemsdijk, Willem H. (Geochimica et cosmochimica acta, 2003)
Under natural conditions, the adsorption of ions at the solid–water interface may be strongly influenced by the adsorption of organic matter. In this paper, we describe the adsorption of fulvic acid (FA) by metal(hydr)oxide surfaces with a heterogeneous surface complexation model, the ligand and charge distribution (LCD) model. The model is a self-consistent combination of the nonideal competitive adsorption (NICA) equation and the CD-MUSIC model. The LCD model can describe simultaneously the concentration, pH, and salt dependency of the adsorption with a minimum of only three adjustable parameters. Furthermore, the model predicts the coadsorption of protons accurately for an extended range of conditions. Surface speciation calculations show that almost all hydroxyl groups of the adsorbed FA molecules are involved in outer sphere complexation reactions. The carboxylic groups of the adsorbed FA molecule form inner and outer sphere complexes. Furthermore, part of the carboxylate groups remain noncoordinated and deprotonated.